Nation-wide vector surveillance on Zika and Dengue did not indicate transmission of the American lineage-pandemic Zika virus in India. (December 2021) - Kumar, N. Pradeep; Kumar, Ashwani; Panneer, D.; Abidha, S.; Muthukumaravel, S.; Sankari, T.; Ajithlal, P.M.; Mathew, Jessu; Koothradan, Suhana; Paramasivan, R.; Muniyaraj, M.; Singh, Himmat; et al.
Abstract: Objectives: Following the Public Health Emergency of International Concern declared on Zika by the World Health Organization during 2016, the Indian Council of Medical Research carried out nationwide vector surveillance for Zika and Dengue viruses (ZIKV and DENV) in India as a preparedness measure in 2016–19. Methods: High-risk zones distributed to 49 Districts in 14 states/union territories were included in the study. Seven ICMR institutions participated, following a standard operating protocol. Aedes specimens sampled weekly were processed by multiplex reverse transcriptase-polymerase chain reaction (RT-PCR) for ZIKV/DENV and random samples crosschecked with real-time RT-PCR for ZIKV. Results: Altogether, 79 492 Aedes specimens in 6492 pools were processed; 3 (0.05%) and 63 (0.97%) pools, respectively, were found positive for ZIKV and DENV. ZIKV infections were recorded in Aedes aegypti sampled during the 2018 sporadic Zika outbreak in Jaipur, Rajasthan. However, these belonged to the Asian lineage of the virus, already circulating in the country. Both Ae. aegypti and Aedes albopictus distributed to 8 states/union territories were found to be infected with DENV. Both sexes of Ae. albopictus were infected, indicating transovarial transmission. Conclusion: This investigation evinced no active transmission of the American lineage-pandemic Zika virus in India during the pandemic period.